Penerapan Quality of Service (QoS) pada Fiber to the Home (FTTH) di Graha Sudirman Indramayu - Willy Permana Putra; A. Sumarudin; Kurnia Adi Cahyanto (IKRA-ITH ABDIMAS, 2023)
Graha Sudirman housing started its construction in 2012, Graha Sudirman itself is located in thecenter of Indramayu city. Graha Sudirman housing has implemented an internet network to support ITbasedsmart housing. In this case, it is still based on simple fiber optics. This network has limitations interms of QoS on the client side. One of the initiators of IT-based smart housing is the housing coordinator,namely Mr. Khaerul Anam. In this Community Service program, we try to apply FTTH technology inGraha Sudirman housing to support IT-based smart housing. This service is expected to assist partners inimplementing IT-based smart housing programs both in terms of infrastructure and applications. From theresults of the implementation, the fiber optic attenuation output in each house ranges from -13dB to -25dB,this is due to many factors ranging from the type of fiber cable to the splicing or installation process. Forspeed, from -13dB to -25dB, you can still get 902 Mbps of bandwidth. This speed will decrease if it exceeds-29dB and above, even for connections it can be lost.